Survival, persistence, and regeneration of the reindeer lichens, Cladina stellaris, C. rangiferina, and C. mitis following clearcut logging and forest fire in northwestern Ontario - Webb, Elizabeth T. (Rangifer, 1998)
The responses of the reindeer lichens (Cladina stellaris, C. rangiferina, and C. mitis) to logging and fire were compared in lichen-rich forest stands in northwestern Ontario. In the summer of 1992, reindeer lichen cover, in total and by species, was visually estimated and detailed notes were taken on reindeer lichen conditions, modes of reproduction, and substrate use on 34 undisturbed, burned, or logged sites. While virtually no reindeer lichens survived forest fire, much of the reindeer lichen cover remained after logging. Reindeer lichen cover increased with time since fire. Total reindeer lichen cover was not correlated with time since logging. Fragment growth was found to be an important mode of reproduction on logged sites, and occurred with greater frequency on logged sites than on burned sites. Colonization of organic substrates by reindeer lichens was observed on both logged and burned sites.